Dynamic trust evaluation model based on evaluation credibility in cloud computing - Lin ZHANG; Kai-li RAO; Ru-chuan WANG (Tongxin xuebao)
Considering the problem that cloud users will select a trusted cloud service provider, a dynamic trust evalua-tion model based on evaluation credibility was proposed.This model divides the ability of cloud service provider and the one of the user's requirments into many ranks, which can effectively solve the potential damage caused by the dynamic change in the ability of cloud service providers. A dynamic mechanism of trust changing about time-window was estab-lished. During the calculation of credibility, the user's evaluation credibility was used as the trust weight. The calculating accuracy of the recommended behavior credibility was improved by introducing the evaluation credibility and evaluation similarity. Simulation results show that the model results are closer to the cloud service provider's actual trust value, and can resist the attack of malicious cloud users effectively.